Growing poplars for research with and without mycorrhizas - Müller, Anna; Volmer, Katharina; Mishra-Knyrim, Manika; Polle, Andrea (Frontiers in Plant Science, 2013)
During the last decades the importance of the genus Populus increased because the poplar genome has been sequenced and molecular tools for basic research are available. Furthermore, poplar species occur in different habitats and harbour large genetic variation, which can be exploited for economic applications and for increasing our knowledge on the basic molecular mechanisms of the woody life style. Poplars are, therefore, employed to unravel the molecular mechanisms of wood formation, stress tolerance, tree nutrition and interaction with other organisms such as pathogens or mycorrhiza. The basis of these investigations is the reproducible production of homogeneous plant material. In this method paper we describe techniques and growth conditions for the in vitro propagation of different poplar species (Populus × canescens, P. trichocarpa, P. tremula and P. euphratica) and ectomycorrhizal fungi (Laccaria bicolor, Paxillus involutus) as well as for their co-cultivation for ectomycorrhizal synthesis. Maintenance and plant preparation require different multiplication and rooting media. Growth systems to cultivate poplars under axenic conditions in agar and sand cultures with and without mycorrhizal fungi are described. Transfer of the plants from in vitro to in situ conditions is critical and hardening is important to prevent high mortality. Growth and vitality of the trees in vitro and outdoors with and without ectomycorrhizas are reported.